أثر الحوافر المعنوية على أداء العاملين في المؤسسة الاقتصادية - قدة, حياة; نعرورة, بوبكر (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة على معرفة أثر الحوافز المعنوية في أداء العاملين على مستوى المؤسسة الاقتصادية، وكذا تحديد الفروق في مستوى الحوافز المعنوية في المؤسسة تبعا لمتغيرات العمر، المستوى التعليمي، الوظيفة والأقدمية. شملت عينة الدراسة 31 عامل من الوكالة الوطنية لدعم وتشغيل الشباب بالوادي، واعتمدت الدراسة على الاستبيان كأداة البحث، وتوصلت الدراسة إلى مجموعة من النتائج من بينها ووجود علاقة تأثير ذات دلالة إحصائية بين الحوافز المعنوية وأداء العاملين في المؤسسة محل الدراسةـ كذالك لا توجد فروق ذات دلالة إحصائية بين مستوى الحوافز المعنوية والمتغيرات الاسمية لأفراد العينة المبحوثة. الحوافز ؛ الحوافز المعنوية ؛ أداء العاملين. This study aims to know the effect of moral incentives on the performance of workers at the level of the economic institution, as well as to identify differences in the level of moral incentives in the institution according to the variables of age, educational level, function and seniority. The study sample included 31 workers from The National Agency for the Support and Employment of Youth in Eloued, and the study relied on the questionnaire as a research tool, and the study reached a set of results from among them and the presence of a statistically significant effect relationship between moral incentives and the performance of workers in the institution under study - also there are no statistically significant differences between The level of moral incentives and nominal variables of the respondents. Keywords: Incentives; Moral incentives; Staff performance.
مقال
Keywords: الحوافز ; الحوافز المعنوية ; أداء العاملين.